O sentido do trabalho para tutores em educação a distância - Neves, Yviana Wanderley Cidreira (2018)
Objective - This work intends to contribute to the scientific knowledge investigating the meaning of work for professionals who work in distance learning mentoring activities concerning professional education within a private higher education institution. Methodology - The qualitative research was conducted through a single case study. The unit of analysis consisted of 30 tutors of distance education from an institution of Higher Education. The data collection occurred between May and June of 2018, in Rio de Janeiro / RJ. The sample was obtained by convenience and data collection was carried out through semi-structured interviews and non-participant observation of the environment. Subsequently, the interviews were transcribed and submitted to discourse analysis. The content of the interviews was analyzed from the categories defined in the work of Morin (2001). Additionally, were found new categories, typical of the mentoring of distance education that emerged from the speeches of the interviewees. Results: This study identified that the meaning of work for distance learning tutoring professionals is similar to that of the categories presented in the research of Morin (2001). More specifically, in the case of these professionals, it has shown that is not the first, nor the only career option of the interviewees and this fact is attributed to the feeling of devaluation of this professional category, whose legal issues are not yet clearly defined. Also, it was found that the absence of a sense of belonging by the interviewees, who attribute this fact to the lack of employment bond with the institution. Limitations - This research is limited to the area of administrative sciences and was held in the context of a higher education institution. Applicability of work - For practitioners the results can help in understanding the meaning of work for distance education tutoring professionals. In this way, decision makers can incorporate into their policies within organizations a new knowledge to increase motivation, facilitate the training and performance evaluation. For the Academy expands the discussion of the meaning of work in a context not yet explored in the literature. Moreover, for tutors, the results allow them to reflect on everyday life at work and so may seek to improve the quality of life also in this environment. Contributions to society - This research can guide and encourage future studies and debates on existing theories on the topic meaning of work, which may contribute to discussion by professionals, students, and managers involved in the area of distance education on the role of each one in the consolidation of this modality of education within the country. Originality - The research offers a new perspective on the meaning of work for tutors since this type of education still has not been investigated in depth. Further, a survey about the meaning of work in this context - mentoring in distance education - had still not been carried out up to the moment.